AB0596 Systemic Lupus Erythematosus Patients with Past Neuropsychiatric Involvement is Associated with Worse Cognitive Impairment: A Longitudinal Study. (9th June 2015) - Gao, Y.; Lau, E.; Wan, H.; Lo, Y.; Mok, M.Y.
Abstract : Background: Studies on cognitive impairment in patients with past history of neuropsychiatric lupus (NPSLE) were often confounded by psychiatric and other disease related factors. Objectives: This study aims to evaluate cognitive function in NPSLE patients in relation to psychiatric factors longitudinally in comparison to matched controls. Methods: NPSLE patients and matched disease and healthy controls were examined by full battery of neurocognitive tests that covered 8 cognitive domains at 2 time-points 12 months apart. Depressive and anxiety symptoms were measured by HADS. Results: 18 NPSLE and 18 patients with systemic lupus erythematosus (SLE) who had no previous cerebral involvement (non-NPSLE) matched to age, sex and disease duration, and 16 age- and sex- matched healthy subjects were recruited. NPSLE patients consistently reported more cognitive symptoms and anxiety symptoms than non-NPSLE patients over both time-points. NPSLE patients had significantly worse simple and complex attention, memory, reasoning and visuospatial processing compared to non-NPSLE patients, among which memory and simple attention remained significantly impaired after adjustment to confounders. Anxiety and depressive symptoms were found to have an effect on raw scores but not demographically adjusted T score of neurocognitive tests. Unlike non-NPSLE subjects, NPSLE patients also failed to demonstrate practice effect upon re-evaluation over 12 months. Both NPSLE and non-NPSLE patients had worse memory than healthy subjects, with deficiency in more memory tests for NPSLE patients. Conclusions: NPSLE patients had significantly worse and persistently impaired cognitive functions involving memory, visuospatial processing and complex attention and impaired learning compared to non-NPSLE patients over 12-month re-assessment. Disclosure of Interest: None declared